Lionfish on the loose: Pterois invade shallow habitats in the tropical southwestern Atlantic - Soares, Marcelo O.; Feitosa, Caroline V.; Garcia, Tatiane M.; Cottens, Kelly Ferreira; Vinicius, Bruno; Paiva, Sandra Vieira; Duarte, Oscar de Sousa; Gurjão, Lívio Moreira; Silva, Grasielle Dayse de Vasconcelos; Maia, Rafaela Camargo; Previatto, Diego M.; Carneiro, Pedro B. M.; et al. (Frontiers in Marine Science, 2022)
Lionfish (Pterois spp.) evolved in the Indo-Pacific with predators and prey and invaded regions (e.g., the Caribbean Sea and Mediterranean) where no such balance yet exists. In 2020, four lionfish were recorded on mesophotic reefs of the Amazon offshore Coast and Fernando de Noronha Archipelago. However, until now, there were no records of invasive lionfish in Brazilian nearshore waters or even such a high number of individuals. In this article, we report the continuing invasion process along the Brazilian Province by multiple sightings (72) of lionfish from March to May 2022 in estuaries, seagrass beds, and artificial and natural reefs across 240 km of the Brazilian coast. These are the first records of lionfish in coastal northeast Brazil and the shallowest records (1–16 m) from South Atlantic tropical waters. The largest simultaneous records of lionfish in breakwaters, fishing weirs, and marambaias (artificial reefs used as fishing grounds) on the Brazilian Northeastern coast indicate that these man-made structures are suitable habitats for this species. Most of the lionfish (58%) were recorded in artificial reefs and fishing weirs. Moreover, the detection of invasions in marginal reefs, estuaries, and two marine protected areas characterized by moderately turbid water and high sedimentation rates highlights the adaptability of the lionfish, making it extremely difficult for divers and fishers to capture them. We call for an urgent management plan considering that the invaded tropical region hosts a high level of endemism, and rare and/or cryptic taxa, which increases the risk of impacts since these are primary lionfish prey.